The Growth Potential of Startups over the Business Cycle - Sedláček, Petr; Sterk, Vincent (American Economic Review, 2017)
This paper shows that employment in cohorts of US firms is strongly influenced by aggregate conditions at the time of their entry. Employment fluctuations of startups are procyclical, they persist into later years, and cohort-level employment variations are largely driven by differences in firm size, rather than the number of firms. An estimated general equilibrium firm dynamics model reveals that aggregate conditions at birth, rather than post-entry choices, drive the majority of cohort-level employment variation by affecting the share of startups with high growth potential. In the aggregate, changes in startup conditions result in large, slow-moving fluctuations in employment. (JEL D25, E24, E32, J23, L25, M13)